On China's Trade Surplus - YUAN, Tao.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
China$1 (Bs trade surplus is an essential question, but there are many popular misconceptions about it, a fact that prompted the creation of this book, On China's Trade Surplus. It will help readers to understand the manner in which China$1 (Bs foreign trade and China$1 (Bs role in global trade have developed, and to how to benefit from trade with China. In this book, many hot topics are analyzed, such as: What promotes China$1 (Bs trade surplus? Why doesn$1 (Bt it have a trade deficit? What are the relations between trade frictions and China$1 (Bs trade surplus, and how can trade frictions be reduced? What is the deeper meaning of the U.S. trade deficit with China?s
China's trade surplus: a whole view -- What promotes China's trade surplus -- Why China's trade deficit should not appear -- To reduce trade frictions -- The U.S. trade deficit with China: an excuse.
Keywords: Economics; Economics/Management Science; Trade